2020
DOI: 10.1063/5.0020334
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancing photoresponse at LaAlO3/SrTiO3 interfaces by the nickelate buffer layer

Abstract: Manipulating the photoresponse of two-dimensional electron gas at the interface of complex oxides is attracting tremendous interest because of its potential applications in photoelectric devices. In this study, transport behaviors of LaAlO3/SrTiO3 heterointerfaces tuned by a nickelate buffer layer under light irradiation have been investigated. With the increasing thickness of the buffer layer, the LaAlO3/SrTiO3 interfaces exhibit the metal-to-insulator transition. More importantly, we also observe a substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For examples, Zhang et al reported a magnetic 2DEG at a La 7/8 Sr 1/8 MnO 3 -buffered LAO/STO interface, while a high-mobility 2DEG exceeding 10 000 cm 2 V –1 s –1 at 2 K was declared by inserting La 1– x Sr x MnO 3 at LAO/STO interfaces . We also observed an enhanced photoresponse by 5 orders using the insertion of a NdNiO 3 buffer layer at LAO/STO interfaces . Therefore, it is necessary to study the influence of different thicknesses of buffer layers on a 2DEG.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…For examples, Zhang et al reported a magnetic 2DEG at a La 7/8 Sr 1/8 MnO 3 -buffered LAO/STO interface, while a high-mobility 2DEG exceeding 10 000 cm 2 V –1 s –1 at 2 K was declared by inserting La 1– x Sr x MnO 3 at LAO/STO interfaces . We also observed an enhanced photoresponse by 5 orders using the insertion of a NdNiO 3 buffer layer at LAO/STO interfaces . Therefore, it is necessary to study the influence of different thicknesses of buffer layers on a 2DEG.…”
Section: Introductionmentioning
confidence: 59%
“…Moreover, the 2DEGs exhibit a very sensitive response to external stimuli, like light, electric field, ionic liquid, etc., suggesting potential in electronic and optical devices. , Recent studies have shown that introducing buffer layers at interfaces effectively modifies the crystal and electronic structure, thus manipulating the characteristics of a 2DEG, especially the photoconductivity, , carrier mobility, and magnetic properties . In addition, the different thicknesses of the buffer layer also can tune the transport properties at the interface, such as the metal-insulation transition, photoresponse, , and relaxation time constant . For examples, Zhang et al reported a magnetic 2DEG at a La 7/8 Sr 1/8 MnO 3 -buffered LAO/STO interface, while a high-mobility 2DEG exceeding 10 000 cm 2 V –1 s –1 at 2 K was declared by inserting La 1– x Sr x MnO 3 at LAO/STO interfaces .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23] These complex oxide interfaces provide combined efficiency of different factors, like crystal lattice, orbital, and spin, [24][25][26] which explain the diversity of physical phenomena and sensitive response towards external stimuli. To manipulate the 2DEG in such oxide interfaces, some research studies have adopted different doping methods, like structural modulation by introducing a buffer layer, [27][28][29][30][31][32] and they proved their good capability. However, the discontinuity in the structure and component can naturally lead to some limitations, like localized trap or scattering centers for carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional electron gas (2DEG) at the interface of insulating complex oxides has been drawing tremendous attention ever since its first report by Hwang et al at the interface of LaAlO 3 (LAO) and SrTiO 3 (STO). Such 2DEG shows a lot of significant phenomena, like superconductivity, high carrier mobility, magnetism, Rashba spin–orbit coupling ( SOC ), and sometimes coexistence of them, forming a complex system of quantum coherence that responds to multiple external stimuli. Among these appealing properties of interfacial 2DEG, the magnetism is a strongly desired one, , as it provides a powerful platform to study the spintronics in all-oxide devices. To date, there have been many meaningful works to generate magnetic 2DEGs at the interfaces of complex oxides, like to use a magnetic substrate or capping layer, , to introduce magnetic dopants, , or to insert a magnetic buffer layer into the interface. These works broaden our horizon in condensed matter physics.…”
mentioning
confidence: 99%